Synergy of Potential Sources of Social Welfare and District Social Welfare Workers in Handling People with Social Welfare Problems - Ahmadi Ahmadi; Rachmat Bowo Suharto (Law Development Journal, 2020)
This study aims to determine and analyze the causes. What is meant by social problems and who are people with social welfare problems (PMKS) and potential sources of social welfare (PSKS)? And how can social welfare be realized in the midst of society? This research method used is empirical juridical method. Sources of data use primary and secondary data. Data collection methods are carried out by interviews and literature techniques through literature studies by reading, studying books and related laws and regulations. The problems of this research were analyzed with the theory of democracy, theory of elections and theory of social problems. This result research shows that in overcoming social problems is constrained by the low community participation to participate in handling social problems in the field. Therefore the role of the government is to be able to develop awareness in the community so that the nature of social volunteerism that exists in the community can arise so that the character to help others through individuals and communities and organizations can emerge. If only relying on the government's helping hand through the social programs disbursed, it has not been able to solve or close the gap in social problems that arise in the community. Furthermore, the government must be able to match the existing potentials in the community so that it can be used as a core force in building a network of social pillars in the community.